2020
DOI: 10.1177/1129729820984284
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment following implementation of a vascular access team

Abstract: Background: A vascular access team (VAT) was created in 2018 with the aim of improving vascular access and reducing complications associated with catheters. The impact of the introduction of a VAT in the insertion and maintenance of peripheral insertion central catheters (PICCs) was assessed. The cost-benefit associated with the use of a VAT was evaluated and the satisfaction of patients and professionals interacting with the VAT was measured. Methods: In a prospective study, 275 PICCs inserted by the VAT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
11
0
3
Order By: Relevance
“…We did not assess fiscal impacts of these changes, but several writers have noted previously that significant cost savings can be achieved by allowing PICCs to be placed at the bedside instead of relying on a team of interventional radiologists located in the IR suite. 20,22,30,34 It is also likely that lowered PIV infiltration and CLABSI rates over time contribute to reductions in the cost of care. 3,42 Calculations of this kind are an important area for consideration in future studies of organizational-level changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not assess fiscal impacts of these changes, but several writers have noted previously that significant cost savings can be achieved by allowing PICCs to be placed at the bedside instead of relying on a team of interventional radiologists located in the IR suite. 20,22,30,34 It is also likely that lowered PIV infiltration and CLABSI rates over time contribute to reductions in the cost of care. 3,42 Calculations of this kind are an important area for consideration in future studies of organizational-level changes.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Peripherally inserted central catheters (PICCs) are the preferred choice for longterm central access in neonates due to their extended dwell time, small diameter, and ability to be placed safely and cost effectively. 1,11,19,20 A key concern with obtaining central vascular access in the NICU, however, is time delay. Time delay for central vascular access at any point in the course of treatment can become a factor affecting clinical outcomes for neonates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Van Loon et al11 found that the clinician's anticipation and “gut feeling” of difficult access is a major predictor of failed first attempts. Use of adjunctive vascular assessment tools can lead to improved patient outcomes, higher first-attempt success, decreased pain, shorter procedure time, and increased patient satisfaction, as well as improvements for the facility and staff including improved resource utilization, decreased staff burnout, and improved safety 12. These devices help improve accuracy during phlebotomy, particularly in patients with DIVA.…”
Section: Adjunctive Vascular Assessment Toolsmentioning
confidence: 99%
“…The value of the VAT expands from mitigating preventable events (eg, deep venous thrombosis, infection) to enhancing patient experience (eg, less attempts to place a peripheral device). 9 In addition, better outcomes help curb the financial risks (eg, hospital-acquired condition penalties) 8 and improve hospital ratings. The VAT's role encompasses placing PICCs and guaranteeing the proper selection of the intravascular device and its appropriate use.…”
mentioning
confidence: 99%